Теорії місцевого самоврядування і самоорганізація населення - Мішина, Наталя Вікторівна; Мишина, Наталья Викторовна; Mishina, Natal'ja (My University, 2009)
The article is dedicated to the correspondence of the municipal theory, which is applied in the country's legislation, and the policy about the citizens' self-organization bodies. The author researches the community theory, the state theory and the community-state theory and makes the conclusions about their adept's attitude to the citizens'self-organization bodies. Also the author gives recommendations, which could be applicable in Ukraine: to select the preferable municipal theory on the state level and to harmonize the legislation with this theory. This will have a positive effect on the development of the institute of self-organization in Ukraine.
Мішина Н. В. Теорії місцевого самоврядування і самоорганізація населення / Н. В. Мішина // Наукові праці Одеської національної юридичної академії / голов. ред. С. В. Ківалов ; МОН України, ОНЮА. - Одеса : Юрид. л-ра, 2009. - Т. 8. - С. 163-170.
Keywords: місцеве самоврядування; самоорганізація населення; органи самоорганізації населення; местное самоуправление; самоорганизация населения; органы самоорганизации населения; local government; citizens' self-organization; citizens' self-organization bodies